2015
DOI: 10.1007/s00415-015-7780-x
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid hormone level is associated with motor symptoms in de novo Parkinson’s disease

Abstract: Sympathetic denervation has been observed not only in the myocardium but also in the thyroid of patients with Parkinson's disease (PD). We investigated whether sympathetic denervation as indicated by decreased cardiac (123)I-meta-iodobenzylguanidine uptake is associated with the levels of thyroid hormones and whether the levels of thyroid hormones affect clinical manifestations in patients with PD. The subjects were 75 patients with de novo PD and 20 age-matched healthy controls. We examined the levels of thyr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
13
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 30 publications
4
13
1
Order By: Relevance
“…Also, embelin has considerably shown inhibition of lipid peroxidation and up-regulation of Mn-superoxide dismutase levels. 46 In earlier work Umehara et al 47 reported significantly lower levels of T3 in PD patients with notable motor symptoms which could be associated with the present findings. However, there is a limited information available from patients with aggravated parkinsonism due to hypothyroidism.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Also, embelin has considerably shown inhibition of lipid peroxidation and up-regulation of Mn-superoxide dismutase levels. 46 In earlier work Umehara et al 47 reported significantly lower levels of T3 in PD patients with notable motor symptoms which could be associated with the present findings. However, there is a limited information available from patients with aggravated parkinsonism due to hypothyroidism.…”
Section: Discussionsupporting
confidence: 75%
“…51 Even though there are still many debates regarding the connection between thyroid function and neurodegenerative disease, it seems that the free T3 levels were found to be lower in PD patients particularly with akinetic-rigid motor subtype, whereas TSH levels were lesser in patients with tremor-dominant type or mixed type, signifying a relation of the thyroid hormone level with PD motor signs. 47 Unfortunately we lack convincing studies from PD mice on TSH levels.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to Gpx family, the Dio1-3 mRNA levels are not significantly affected in the brain regions of PD mice. Although hypothyroidism and abnormal thyroid hormone levels are sometimes reported in PD patients [ 26 , 27 ], our results suggest little or no role of Dios in the PD brain. This is indeed not surprising, considering the nature of Dio family members in catalyzing deiodination of thyroid hormone and their relatively low abundance in the brain.…”
Section: Discussioncontrasting
confidence: 65%
“…Liothyronine is a synthetic form of the thyroid hormone triiodothyronine that is used for hypothyroidism [48] . It has been shown that there is an association of low thyroid hormone levels with motor symptoms in Parkinson’s disease [49] . Efavirenz is a non-nucleoside inhibitor of reverse transcriptases and is used for the treatment and prevention of HIV/AIDS [50] .…”
Section: Resultsmentioning
confidence: 99%